To what extent does the size of a ventricular septal defect correlate with haemodynamic data derived from cardiac catheterisation?. Issue 1 (July 1987) - Fukazawa, M; Honda, S; Fukushige, J; Sunagawa, H; Yasui, H; Ueda, K
Abstract : A simplified model based on Gorlin's formula was used to derive an index of the cross sectional area of ventricular septal defects from commonly used cardiac catheterisation data. This index was compared with the area of the defect measured during operation and expressed as a ratio to the cross sectional area of the aorta. The highly significant linear relation (r = 0.94) between this index of the defect area and the size of the defect measured at operation means that the severity of a ventricular septal defect can be assessed from haemodynamic data obtained at cardiac catheterisation.